Teacher classroom interactions and behaviours: Indications of bias. (April 2022) - İnan-Kaya, Gamze; Rubie-Davies, Christine M.
Abstract: In some recent studies, researchers have measured teacher implicit bias and some have shown that teacher bias predicts student academic outcomes. Currently, however, how bias is portrayed to individual students is largely unknown. In this exploratory qualitative study, observations totalling 4 h per participant were undertaken with ten secondary, six intermediate, and four primary teachers in New Zealand. We utilised a thematic analysis approach to identify three themes: "differential nonverbal behaviours", "differential academic interactions" and "differential reactions under the same conditions" that captured teachers' classroom interactions. Our findings suggested that teachers' differential behaviours were mediating teacher bias. This was because teacher bias was recorded in every classroom; however, teachers displayed biased behaviours to varying degrees. Bias was displayed through various nonverbal and academic interactions, and some teachers portrayed their bias by treating some students differently when the situation for all students was the same. Highlights: Teacher bias was observed in every classroom. Teachers displayed bias through nonverbal and academic interactions. Some students were treated differently when the situation for all was the same.